The Mobile Learning Cognitive Counseling Approach for Improving Counseling Practicum Skills Among Undergraduate Students during Covid-19 Pandemic - Budi Astuti; Rizqi Lestari (AL-ISHLAH: Jurnal Pendidikan, 2022)
Students as prospective counsellors need to understand the theory of counselling approaches well to carry out effective counselling practicums. This study aims to develop a mobile learning design for a cognitive counselling approach to improve counselling skills in students. This type of research is research and development. The data collection technique used a questionnaire to determine student and lecturer perceptions of mobile learning media in learning. The sample in this study were 116 students and 38 lecturers of guidance and counselling in Indonesia who were selected using a simple random sampling technique. The results showed that 22.4% of students thought that mobile learning could help the learning process of the counselling approach, and 54% of lecturers thought that mobile learning was needed in learning activities. The mobile learning cognitive counselling approach is a website-based media consisting of 9 features: landing page, login page, initial test, material, final test, chat room, record, developer profile, and contact. The developed mobile learning has been validated by media experts and is declared suitable for learning activities. The researcher tested the effectiveness of mobile learning on 14 students of Yogyakarta State University. The data analysis used the Wilcoxon signed-ranked test and showed the p-value at 0,0000,005, which means that mobile learning effectively improves students' understanding of counselling approaches. Mobile learning contributes as a novelty in guidance and counselling as an innovative media that can be used in the university to deliver content for students in guidance and counselling study programs